Salinity Effect on Germination and Further Development of Parasitic Cuscuta spp. and Related Non-Parasitic Vines - Zagorchev, Lyuben (Plants (Basel), 2021)
Plants are continuously subjected to the unfavorable impact of abiotic stress factors, of which soil salinity is among the most adverse. Although away from direct soil contact throughout most of their lifecycle, stem parasitic plants of the genus Cuscuta, family Convolvulaceae are also affected by salinity. The present study aimed to assess salt stress impact on germination and early establishment of three Cuscuta species, in comparison to related nonparasitic vines of the same family. It was found, that Cuscuta spp. are highly sensitive to NaCl concentration within the range of 200 mM. Germination was delayed in time and reduced by nearly 70%, accompanied by decrease in further seedling growth, ability to infect host plants and growth rate of established parasites. The nonparasitic vines showed similar sensitivity to salinity at germination level, but appeared to adapt better after the stress factor was removed. However, the negative effect of salinity did not fully prevent some of the Cuscuta species from infecting hosts, probably a beneficial characteristic at a species level, allowing the parasite to successfully thrive under the scarce host availability under saline conditions.